2008
DOI: 10.1097/sap.0b013e318168db3e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Incorporation Into Electrospun Nanofibers

Abstract: Nanofibers are an emerging scaffold for tissue engineering. To date no one has reported cell incorporation into nanofibers. Human foreskin fibroblasts and human adipose-derived adult stem cells (hADAS) were grown to confluence, resuspended in phosphate-buffered saline, and then solubilized in polyvinyl alcohol (PVA). Nanofibers were created using an electrospinning technique across an electric potential of 20 kV. Cell interaction with nanofibers was assessed with optical microscopic imaging and scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
2
21
1
Order By: Relevance
“…When a higher proportion of PVA solution was used, fibers were continuously produced, but as the concentration of cells decreased, the analyses of viability became hard to implement. These data agree with a recent study performed by van Aalst et al (2), in which they used electrospinning to perform cell incorporation into nanofibers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When a higher proportion of PVA solution was used, fibers were continuously produced, but as the concentration of cells decreased, the analyses of viability became hard to implement. These data agree with a recent study performed by van Aalst et al (2), in which they used electrospinning to perform cell incorporation into nanofibers.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction of viability observed between the control and PVA groups suggests that the PVA solution has a deleterious effect on cells and that the decrease in cell viability during electrospinning could be caused, at least in part, by the lack of nutrients since as viscosity of the solution can prevent cells from coming into contact with the nutritive medium. In a recent study, van Aalst et al (2), observed a reduction of viability of fibroblasts (30-65%) and stem cells (22%) after the electrospinning process and suggested that this could be explained by the high viscosity of the PVA solution, which changes the shearing effect on cells as they pass through the equipment (2). …”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning is a technique used widely to fabricate micro-and nano-fibrous scaffolds that mimic the native ECM environment to various degrees (Xin et al 2007, Vaquette and Cooper-White 2011, Zhang et al 2009, Brun et al 2011, van Aalst et al 2008. During the electrospinning process, the fibres collect on two-dimensional (2D) plates, resulting in scaffolds composed of consecutive layers of randomly arranged fibrous sheets (Zhang and Chang 2008).…”
Section: Introductionmentioning
confidence: 99%
“…High surface area nano-micro-fibers (NMF) (9) can be created from multiple natural and synthetic materials, (1012) providing 3-dimensional scaffolds that mimic the extracellular matrix (ECM) and promote cellular adherence, proliferation and migration. (13, 14) The ECM has fibers with a wide range of diameters, and include collagens (generally 10–500 nm) and elastin fibrils (100–200 nm) depending on tissue structure, location, and age.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Though the polymers available for electrospinning are numerous, the use of materials with proven implantation histories would be valuable. Individual polymers used in resorbable plating systems have been used to create nanofibers, and include poly-L-lactic acid (PLA), and poly-lactic-co-glycolytic acid (PLGA); (11)(16) however, there are no reports in the literature of any patented resorbable plating systems used for NMF creation.…”
Section: Introductionmentioning
confidence: 99%